Type of Antifungals: Does it Matter in Empirical Treatment of Otomycosis? - Navaneethan, Nagendran (Indian J Otolaryngol Head Neck Surg, 2014)
To evaluate the efficacy of clotrimazole, miconazole and fluconazole in empirical treatment of otomycosis in our tertiary care hospital and to appraise possible better outcome in otomycosis. Two hundred and ninety five patients who presented with clinical otomycosis at our Melmaruvathur Adiparasakthi Institute of medical sciences were incorporated in this study. Two hundred and fourteen patients who satisfied our criteria were recognized and they were randomly alienated into three groups A, B, C. Group A patients were advised to instill clotrimazole ear drops by themselves. Miconazole cream instillation were done by our trained personal in group B patients. Group C patients were advised to use fluconazole ear drops. Patients were educated to keep ear dry and instructed to come for evaluation in first and second week after initial visit. A randomized double blinded prospective study. In the first week, clotrimazole had a good response than miconazole and fluconazole in our patients and in the second week, our patients showed a drastic response in patients instilling flucanozole ear drops compared to those using micanozole and clotrimazole. This better outcome doesn’t show statistical significance since p value is 0.882. Clotrimazole drops, miconazole cream and Fluconazole drops showed almost same therapeutic efficacy in Otomycosis